1998
DOI: 10.1111/0022-1082.00056
|View full text |Cite
|
Sign up to set email alerts
|

Credit Risk in Private Debt Portfolios

Abstract: Default, loss severity, and average loss rates for a large sample of privately placed bonds are presented and compared with loss experience for publicly issued bonds. The chance of very large portfolio losses is estimated and some determinants of such losses are analyzed. Results show ex ante riskier classes of private debt perform better on average than public debt. Both diversification and the riskiness of individual portfolio assets inf luence the bad tail of the portfolio loss distribution. Private placeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(141 citation statements)
references
References 10 publications
4
134
1
2
Order By: Relevance
“…However, in applications of the method, the realism of embedded correlations is limited by the features of the database being used. Major advantages of the Society of Actuaries database used in Carey (1998) are its focus on private debt instruments and its incorporation of actual LGDs for each credit risk event, so that both cross-default and default-LGD correlations typical of loans are captured. However, that database covers a relatively short time period and lacks information about the industry of many borrowers, limiting both the range of correlations reflected in the data and the ability to study the effect of industry diversification on bad-tail loss rates.…”
Section: Some Details Of the Resampling Methods And Its Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in applications of the method, the realism of embedded correlations is limited by the features of the database being used. Major advantages of the Society of Actuaries database used in Carey (1998) are its focus on private debt instruments and its incorporation of actual LGDs for each credit risk event, so that both cross-default and default-LGD correlations typical of loans are captured. However, that database covers a relatively short time period and lacks information about the industry of many borrowers, limiting both the range of correlations reflected in the data and the ability to study the effect of industry diversification on bad-tail loss rates.…”
Section: Some Details Of the Resampling Methods And Its Implementationmentioning
confidence: 99%
“…It is difficult to know the reliability of evidence such models produce about the influence of a given portfolio characteristic on bad tail loss rates and thus on economic capital requirements. This paper uses the Monte Carlo resampling method of Carey (1998) to provide nonparametric empirical evidence about the practical importance to portfolio bad tail loss rates of 3 A similar database available from S&P is also a primary source of parameter values. 3 In this paper, the desirability of prudential regulation of bank capital is taken as given.…”
mentioning
confidence: 99%
“…It can be empirically demonstrated that credit spreads were particularly accurate forecasters of subsequent default rates at the start of 1990 and again at the start of 1991. 7 The credit spread indicator is a commonly used barometer of risk in financial systems and for economic cycles by both the government and banks.…”
Section: The Lead-lag Relationship Of Capital Reservesmentioning
confidence: 99%
“…For an additional 104 bonds, we only had the rating and not the price, one year prior to default. For these bonds, we assumed that their default experience 7 On December 31, 1989 the yield-spread between high yield corporate bonds and ten-year U.S. Treasury bonds was 7.24% and one year later it was 10.50% (Table 3). These were the highest levels for several decades and the subsequent annual default rates (10.1% and 10.3%) were the highest default rates on high yield "junk" bonds ever recorded.…”
Section: Bucket Risk Homogeneitymentioning
confidence: 99%
“…The very large number of loan spells in each loan portfolio allows us to apply a non-parametric Monte Carlo resampling method as in Carey [8], thereby guaranteeing robust results. 2 The organization of the remainder of this paper is as follows.…”
Section: Introductionmentioning
confidence: 99%